Determination of twisting angle of electrospun nanofiber bundle for continuous electrospinning system. Issue 48 (21st August 2017) - Lee, Jung Hun; Gim, Yeonghyeon; Bae, Seonghyun; Oh, Changeun; Ko, Han Seo; Baik, Seunghyun; Oh, Tae Sik; Yoo, Ji Beom
ABSTRACT: Electrospinning continuously produced twisted nanofibers with a convergence coil and a rotating ring collector. The positively charged nozzle was used in the electrospinning process to deposit electrospun fibers of polyacrylonitrile onto a rotating ring collector. By withdrawing the electrospun fibers from the rotating ring collector, it was possible to spin the electrospun fibers yarn. In this study, theoretical approaches and numerical simulations were used to determine the twisting angle of the yarn. Using the equations developed in this study, we performed numerical simulations and compared the experimental results with the numerical simulation results. Mechanical properties of the fiber bundle were analyzed for twisting angle. It was confirmed the relationship among the winding drum, the ring collector, and flux of the fibers mass per time during electrospinning in the developed system. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45528. Abstract :